Pengabdian Masyarakat Internasional: Studi Pelaksanaan Festival Russia in the Heart of Indonesia di MAN 9 Jakarta Timur - Ade Reza Hariyadi; Saefudin Zuhri; Sari Ningsih; Kiky Setyawati; Pretty Failasufa Aziza; Anisa Pramitasari; Achmad Sulistyono; Catarina Cori; Daria Starkova; A. Petukhova A. Petukhova (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
This international community service activity represents a concrete form of educational diplomacy, positioning academic engagement as a medium for the exchange of knowledge, values, and culture between nations. Unlike locally oriented programs, international-based service initiatives facilitate direct interaction among educational institutions, lecturers, university students, and secondary school students from diverse cultural backgrounds. This activity was conducted at MAN 9 East Jakarta on October 20, 2025, by lecturers and students from Universitas Krisnadwipayana in collaboration with the Embassy of the Russian Federation. The program involved all students of MAN 9 East Jakarta as participants. The service method was implemented in three main stages: pre-activity preparation, activity implementation, and post-activity evaluation. The program focused on introducing the Russian language, culture, and education system through interactive presentations and discussions. The results indicate a significant increase in students’ understanding of Russian studies, as reflected in their enthusiasm and active participation throughout the sessions. Direct engagement with international academic representatives provided a meaningful global learning experience and stimulated students’ interest in pursuing higher education and international collaboration. Institutionally, this initiative strengthened the role of the Faculty of Administrative Sciences, Universitas Krisnadwipayana, as a facilitator of internationally oriented community service and reinforced sustainable cooperation with Ural State Pedagogical University. Student involvement also contributed to the development of organizational and intercultural competencies.